Prevalence of anaemia and its associated factors among the undergraduates of the Faculty of Allied Health Sciences, University of Jaffna - Hennayake, S.H.; Samarakoon, S.A.O.U.; Thennakoon, T.M.B.S.; Sathees, S.; Karunaithas, R. (Faculty of Allied Health Sciences, University of Jaffna, 2023)
Introduction: Anaemia is one of the most common public health concerns worldwide. Although community-based studies are ongoing throughout Sri Lanka, there is a lack of contemporary data on the prevalence of anaemia among university students. Objective: To determine the prevalence and associated factors of anaemia among the undergraduates at the Faculty of Allied Health Sciences, University of Jaffna. Methodology: The cross-sectional descriptive study was carried out among 341 undergraduates. Ethical clearance for the study was obtained from the ethical review committee of the Faculty of Medicine, University of Jaffna. Following informed consent, blood samples were collected, and haemoglobin estimation was performed by the cyanomethaemoglobin method. A self- administered questionnaire was used to assess the factors regarding anaemia. Statistical analyses were performed using the statistical package for the social sciences version 15, and the P value <0.05 was considered statistically significant. Results: Amongst the 341 participants, 63.9% were female, representing a male to- female ratio of 1:1.77. Furthermore, 44.3% and 55.7% of participants were aged between 20-24 and 25-29 years, respectively. The haemoglobin estimations revealed that 23.2% of the undergraduates were anaemic based on the World Health Organization criteria. Among the anaemic students, the proportion of females was markedly high (98.7%). Statistical analysis revealed that following factors were significantly associated with the anaemia among undergraduates; irregular exercise pattern (p=0.015), exercise less than 20 minutes per day (p=0.018), and consumption of green leaves less than 4 times per week (p=0.03). Conclusion: The prevalence of anaemia among undergraduates at the Faculty of Allied Health Sciences, University of Jaffna, was high. Focused education and awareness programs for the prevention of anaemia among undergraduates are recommended. Such programs should include the associated factors identified in this study.
Keywords: Anaemia; Undergraduates; Risk Factors; Faculty of Allied Health Sciences